2020
DOI: 10.1007/s10762-020-00739-6
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz Conductivity Analysis for Highly Doped Thin-Film Semiconductors

Abstract: The analysis of terahertz transmission through semiconducting thin films has proven to be an excellent tool for investigating optoelectronic properties of novel materials. Terahertz time-domain spectroscopy (THz-TDS) can provide information about phonon modes of the crystal, as well as the electrical conductivity of the sample. When paired with photoexcitation, optical-pump-THz-probe (OPTP) technique can be used to gain an insight into the transient photoconductivity of the semiconductor, revealing the dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 35 publications
3
42
1
1
Order By: Relevance
“…1 ). The presence of such phonon modes is known to result in a series of distortions in the THz photoconductivity spectra, including artifacts 30 , 31 . The distinctive derivative shape on the real part of the spectrum evident in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 ). The presence of such phonon modes is known to result in a series of distortions in the THz photoconductivity spectra, including artifacts 30 , 31 . The distinctive derivative shape on the real part of the spectrum evident in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Upon addition of tin fluoride to the perovskite during deposition, a similar transmission to that of the bare quartz substrate is recovered, indicating negligible conductivity of the thin film. Using an analysis of THz transmission through these thin films, 19 , 51 we determine a background doping density of 5 × 10 19 cm –3 for the FA 0.83 Cs 0.17 SnI 3 film without tin-fluoride additive. Existing studies evaluating tin vacancy suppression methods in tin-halide perovskites have found that the minimal doping levels achievable through tin-fluoride addition in these materials are >10 17 cm –3 .…”
Section: Resultsmentioning
confidence: 99%
“…We note that the conductivity transients shown in Figures 2 B and 3 represent spectral averages of THz conductivity over the probe’s bandwidth. 51 …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in Equation ( 8) the assumption of a small change in the transmission is used. Therefore, in the case of doped and highly conductive samples, the full expression has to be used: [139,140] σ…”
Section: Doped and Highly Conductive Samplesmentioning
confidence: 99%
“…It was found that Equation ( 3) is suitable only for materials with conductivity up to 10 4 Ω −1 cm −1 , above which the large complex refractive index invalidates the assumption of negligible optical thickness. [140] In highly doped thin films with high dark conductivity, the approximations (Equation ( 8)) result in a significant underestimate of the photoconductivity, and Equation ( 9) must be used.…”
Section: Doped and Highly Conductive Samplesmentioning
confidence: 99%